The Ethics of Marriage Law in Islam, Catholicism and Protestantism: A Comparative Interfaith Analysis - Mutiara, Zahro; Aris Priyanto (Yayasan Insan Cendekia Nusantara, 2025)
Background Study: Marriage is widely regarded as a foundational social institution that sustains moral order, regulates social relations, and preserves cultural continuity across civilizations and major religious traditions. Islam, Catholicism, and Protestant Christianity each conceptualize marriage as a sacred and morally binding union, yet they articulate its purposes, ethical boundaries, and legal implications in distinct ways. Methods: This study employs a qualitative library-based method, drawing on primary religious texts—the Qur’an, the Bible, and Catholic magisterial documents—alongside scholarly literature on religious ethics and family law. Through systematic textual comparison, the study identifies core ethical principles and examines their similarities and divergences across the three traditions. Key findings: reveal that Islam, Catholicism, and Protestant Christianity share several universal ethical values—commitment, fidelity, responsibility, and justice—while differing in doctrinal interpretations of marital permanence, divorce, gender roles, and reproductive ethics. Catholicism affirms the indissolubility of marriage as a sacrament; Islam upholds marriage as a sacred contract yet permits divorce under regulated conditions; and Protestant Christianity adopts a covenantal framework that allows pastoral flexibility, including divorce in exceptional cases. Contributes: to interreligious ethical discourse by highlighting convergent moral principles that can support dialogue in plural societies, particularly in contexts where interfaith marriage remains contested. Conclusion: the research underscores that despite doctrinal differences, the three religions maintain shared ethical foundations that can strengthen social harmony and enrich contemporary discussions on family ethics and interreligious understanding.